Indicators of strength, oxidative stress, and muscle damage in Paralympic powerlifting athletes undergoing variable resistance training - Edson Lucas Monteiro Vieira; Felipe J. Aidar; Georgian Badicu; José Uilien de Oliveira; Gildo Francisco dos Santos Filho; Seifeddine Brini; Jymmys Lopes dos Santos; Seifeddine Brini Esteban Aedo-Muñhoz; Ciro José Brito (Sport Sciences for Health, 2026)
Abstract Introduction Variable resistance strength training (VRT) has been gaining notoriety in the physical preparation of Paralympic Powerlifting (PP) athletes. PP is a strength sport and training tends to increase levels of Oxidative Stress (OS) and Muscle Damage (MD). Objectives This study aimed to analyze the use of chains as a training method with variable resistance (TRV) and the traditional method with invariable resistance (TRAD) on peak torque (PT), rate of torque development (RTD), biomarkers of oxidative stress (EO), and muscle damage (MD) after a PP training session. Methods Fourteen PP athletes were analyzed, age (28.00 ± 5.64), body weight (82.00 ± 23.93), and 1RM (141.43 ± 47.43). The study was carried out in three consecutive weeks: in week (1), the familiarization and 1RM test occurred, and in weeks (2) and (3) in the pre- and post-training moments (immediately after, 24 h and 48 h after), the PT, RTD, EO, and DM were evaluated. The training consisted of five sets of five repetitions at 80% of 1 Repetition Maximum (1-RM) in the bench press. Results For PT, there was an intraclass difference with the use of the chains between the moment before (462.73±94.23) and the moment after (368.48±119.47, “ a ” p =0.004), and between the moment after (368.48±119.47) and 48 h (444.96±111.25, “ b ” p =0.027, η2p=0.309, high effect). There was a difference at the moment after between traditional training (440.98±116.38) and with the use of chains (368.48±119.47, “ c ” p =0.022). There was also a difference between the traditional (500.99±103.67) and with chains (420.36±114.84, “ d ” p =0.004) at the 24 h time point. There was also a difference at the 48-h time point between the traditional (502.90±122.89) and chains (444.96±111.25, “ e ” p